Exploring competencies of environmental health students in South Africa> Insights from work-integrated learning - Daries, L.; Hudson, L.; Reddy, L. (South African Journal of Higher Education, 2025)
Although the value of work-integrated learning is well documented, limited reports showcase the students’ perspectives. Self-perceived competencies gained by undergraduate Environmental Health (EH) work-integrated learning (WIL) students from a University of Technology in South Africa were obtained through in-depth focus group discussions and analysis of their workplace reflection journals. The Legitimation Code Theory Specialization dimension guided the qualitative data analysis. The analysis uncovered a tension between current assessment criteria and tasks, professional verification and auditing criteria for workplace learning, and real-world competence norms. Exploring this tension revealed a shift in students’ competency focus, fluctuating between conceptual knowledge for classroom success, process- and procedural skills for the professional body evaluation, and a combination of knowledge, skills and behaviours for the workplace. This shift reveals ambiguity, limitations and biases in current assessments favouring the assessment of knowledge and skills. Uncertainty in graduates’ professional identity may further exacerbate the prevailing misconceptions about the EH profession and its contribution to public health among allied health professionals and within society. This research confirms that knowledge and skills are essential in EH practice. However, these are limited as the comprehensive competency range includes soft skills, i.e. professional behaviours consisting of attitudes and values.